Macroprudential policy spillovers in international banking groups. Beggar-thy-neighbour and the role of internal capital markets - Ponte Marques, Aurea; Vila Martín, Diego; Salleo, Carmelo; Cappelletti, Giuseppe (Journal of Banking & Finance, 2025)
Beggar-thy-neighbour in macroprudential policy? This paper studies the impact of macroprudential policies – specifically OSII buffers – on banking groups and their cross-border operations. Using granular data from three confidential databases, we present the first evidence on how banking groups respond to changes in capital requirements. Our findings reveal that: (i) consolidated parent banks constrained by OSII buffers cut back on debt and equity holdings in their foreign subsidiaries, altering global financial structures; (ii) subsidiaries with reduced funding and equity from their parent show a notable decline in lending to non-financial corporations; and (iii) overall, cross-border subsidiaries of OSII-constrained banks exhibit reduced lending and risk-taking towards non-financial corporations, hinting at a role of these subsidiaries in propping up the group’s consolidated capital buffers. While higher capital buffers enhance financial stability by curbing excessive risk-taking, they also constrain the funding and lending capacities of foreign subsidiaries, disrupting local credit markets and creating a “beggar-thy-neighbour” problem. Policymakers need to balance these impacts with the benefits of financial integration.